A comparative study of four rumen buffering agents on productive performance, rumen fermentation and meat quality in growing lambs fed a total mixed ration. (1st March 2019) - Alhidary, I. A.; Abdelrahman, M. M.; Elsabagh, M.
Abstract : Controlling rumen fermentation using buffering agents could contribute to enhancing ruminant productivity and performance. This study was realized to investigate the effect of dietary supplementation of AcidBuf, sodium bicarbonate, calseapowder and WMC seaweed (Utva Lactuca extra) on the animal performance, volatile fatty acids, rumen pH, rumen histology and carcass characteristics of growing male Awassi lambs. A total of 60 lambs was divided into five groups. One group served as a control and fed only on a concentrate diet without any buffering, whereas the other four groups were fed the concentrate diet supplemented with 0.4% AcidBuf (Buf1), 0.4% AcidBuf plus sodium bicarbonate, 50 : 50 (Buf2), 0.4% calseapowder (Buf3) or 0.4% WMC Seaweed (Buf4) for 98 days. The feed conversion ratio was ( P <0.05) improved in Buf2 compared to the control and other treatment groups. The propionic acid decreased, whereas butyric acid was increased in the treatment groups ( P <0.05) compared to the control. The pH of the rumen fluid and the length of submucosa were ( P <0.05) higher in Buf4 and Buf1, respectively, compared to the control. Hot and cold carcass weights were ( P <0.05) higher in Buf4 compared to Buf1. Lean meat percentage and rib eye area were ( P <0.05) higher in Buf4; while the fat percentage was ( P <0.05) lower in Buf2 and Buf4 groups compared to the control. The lightness and yellowness of meat were ( P <0.05) higher in Buf1 and Buf4 compared to the control. The meat pH was ( P <0.05) higher in Buf3 and Buf4 compared to Buf2 (at 1 h) and control (at 24 h). The visceral depot fat (%) was reduced with Buf3 and Buf4 compared to the control. The results indicated that dietary supplementation of different buffering agents improved feed efficiency, rumen pH, carcass characteristics and decreased the body fat in growing Awassi lambs.